Measuring Equilibrating Forces of Financial Ratios. - Davis, Harry Zvi; Peles, Yoram C. (The Accounting Review, 1993)
We test several categories of ratios–short-term liquidity, performance measures, earnings per share (EPS), capital structure, and the gross margin ratio-to determine if they have equilibrium values or follow a random walk. For ratios with an equilibrium value, the speed at which the ratio returns to equilibrium from out-of-equilibrium conditions is measured. Since equilibrating forces may differ with firm size, we also test for differences in adjustment speeds between small and large firms. An accounting ratio may have an equilibrium value if management targets a certain ratio so that any deviation from the target causes management to initiate actions that will return the ratio to target. Also, although management may not be targeting a ratio, the interaction of management's actions with external market industry forces may lead to an equilibrium value. We investigate the total adjustment over time and then assess both the relative adjustment speed and the relative weights of the two main equilibrating forces: industry and management. The statistical technique used allows each firm to have its own, unknown equilibrium value. In addition, we remove an important sampling bias in measuring the autocorrelation coefficient. The results show that when firms experience a liquidity shock, equilibrating forces counterbalance a little more than a third of the shock in the next period. This finding suggests that firms' liquidity ratios have a fast adjustment to equilibrium values. EPS ratios also have a high adjustment rate to equilibrium value; about one-third to one-half of the shock is adjusted within one period. For performance measures (net operating income over sales or assets), for the equity to debt and gross margin ratios. the findings imply a relatively long adjustment process to equilibrium values. Supplementary tests suggest that smaller firms adjust their ratios to the optimal target more swiftly than large firms. Separating the ratios' total adjustment effect into industry and management components provides evidence that the adjustment rates differ for different industries. On average, the management adjustment is faster than the industry effect. A weighting measure suggests that both industry and management contribute a significant share to the total adjustment. Tests of the predictive power of the model show that historical control of performance ratios is correlated with future actual performance. Also, firms that were acquired showed better than average control of their liquidity and performance ratios and showed a destabilization of their equilibrium EPS ratios. Finally, comparing the adjustment rate with a sample of firms from an earlier time period shows a stability of the adjustment behavior over time. Information about the existence of equilibrium ratios and their adjustment speeds can help predict future values or events, and identify firms in special categories, for example, firms that will be acquired. It can also help in the evaluation of managerial actions insofar as managers have control over aspects of the financial ratios examined.